SAR distribution of non-invasive hyperthermia with microstrip applicators on different breast cancer stages - Wong Vei Ling; Kasumawati Lias; Norlida Buniyamin; Hazrul Mohamed Basri; Mohammad Zulkaranen Ahmad Narihan (Institute of Advanced Engineering and Science, 2021)
This paper presents the microstrip antenna with different applied frequencies used as a non-invasive hyperthermia applicator. This non-invasive hyperthermia applicator is introduced to clarify the sufficient heat distribution on the treated tissue for different breast cancer stages. 57 mammogram breast cancer images from early-stage to stage-3 are analyzed to obtain the required penetration depth and focus position distance. Then, the simulation-based experiment is carried out to observe the heating distribution on different stages of cancer with two different operating frequencies; 915MHz and 2450MHz. Also included in this paper is the prediction on the period for hyperthermia treatment planning execution. Based on the results, various penetration depths are obtained when different operating frequencies are applied. 915MHz antenna showed better results when compared to 2450MHz, where microstrip applicator with 915MHz is able to heat cancer at stage-1, stage-2, and stage-3 with good penetration depth and focus position distance, while 2450MHz only performed well in early-stage cancer. Meanwhile, different stages require various periods of time. From the results, the shortest period for hyperthermia execution simulated in the early-stage and then followed by stage-3, stage-2, and the longest period is in stage-1.